Unveiling the enigma of myxoid liposarcoma: diagnostic challenges and multidisciplinary triumphs in limb-salvage surgery - Nasir, Ikhwan; Yeap, Boon Tat; Koo, Thai Hau; Paul, Aaron Gerarde; Zakaria, Mohd Hazeman (Elsevier BV, 2025)
Liposarcoma is a rare soft-tissue sarcoma accounting for about 5% of adult cases; myxoid liposarcoma is the second most common subtype and typically arises in the lower extremities (especially the thigh). We report the case of a 48-year-old woman who presented with a rapidly enlarging, painful mass in the left thigh over 1 year, which was confirmed to be a myxoid liposarcoma on histopathological examination. The patient underwent wide local excision of the tumor with clear margins; she had an uncomplicated postoperative course and remained disease-free at 6 months of follow-up. This case highlights the importance of thorough imaging evaluation and biopsy for accurate diagnosis of soft-tissue masses, as well as the need for complete surgical resection and diligent long-term surveillance in myxoid liposarcoma.